DETERMINATION OF WAITING TIME IN PATIENTS VISITING GENERAL MALE AND FEMALE OUTDOOR CLINICS: Waiting Time in Patients Visiting Outdoor Clinics - Hussain, Khalid; Farid, Muhammad; Masood, Jovaria (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine waiting time of patients visiting general male and female outdoor clinics of 01 MountainMedical Battalion, Bagh.Study Design: Descriptive cross sectional study.Place and Duration of Study: The study was carried out at 1 Mountain Medical Battalion Bagh, from Dec 2016 toFeb 2017.Material and Methods: One hundred and ninety patients selected out of all patients visiting general male andfemale outdoor clinics during working days were included in this study. Lottery method was used to select tenpatients daily in the study period and these were then scrutinized to include those fulfilling the inclusion criteria.Waiting time to get registered, consultation and total waiting time was noted. Data collected was entered andanalyzed using Statistical Package for Social Sciences (SPSS) version 17; Independent sample t-test was used tocompare means between samples with the level of statistical significance set at 5% (p